Analysis of the training workload plan for judo competitors - Sterkowicz, S.
The physiological background to combat in competitions and the exercises which simulate combat in terms of objective structure (the information domain) and time structure (the energy domain) lies in the lactic acid energy changes (range 4). Hence methods engaging these mechanisms were the methods predominantly applied in the training curricula. The data quoted in the literature show that for competitors in Poland's national team the lactate concentration following combat lay in the range from 15.2 to 17.3 (5). Galadis noted a lower LA concentration, 10.4 mmol/l, for 10 competitors in a university team. This might have been associated with a lower level of sports achievement (according to Eaton -3). Judo combats may finish before the regulation time of 5 minutes is up, and hence it would be advisable to monitor the rate of increase for LA concentration during the exertion (Figure 3). The coefficient for LA concentration prior to combat amounted to 2.52 (SE) 0,66. After 75 seconds of exertion it was 5.98 1.19; 10.20 0.97 after 150 seconds; 10.84 0.71 after 225 seconds; and 11.22 1.22 mmol/l after 300 seconds of combat. After 120 seconds of rest LA concentration was 10.10 0.97; and after five minutes' rest it was 10.40 0,87 mmol/l (3). Judo competitors in the high achievement range should be characterized by an ability to work in conditions of fairly high muscle acidity. This is why training methods are selected which simulate combat in terms of their nature and intensity, that is in range 4 (as shown in the TREOB-4 analysis). The time allocated for general in the TS Wisla club was almost equal to the time set aside for special methods; while the proportion of oriented exercises in the full training workload was negligible. By comparison, in cross-country skiing, which calls for a high level of development in competitors' oxygen potential, the largest contribution has been observed to come from methods enhancing the serobic mechanism of energy change (in range 2), and the smallest from exercises stimulating the glycolytic processes (4). A definitive answer to the question of the alleged correlation between the achievements and workloads effected by TS Wisla judoists during training sessions in 1994 and 1995 would be highly interesting. Whereas the points won by this team in 1995 were indeed greater than what they achieved in 1994 in terms of the structure indices observed (0.646 > 0.354; p. < 0.05), it would nevertheless be unreasonable to attribute this fact merely to different proportions of training workload. While the combats fought in the 1994 training cycle may be regarded as a dependent variable, ignoring these highly specific workloads in a retrospective analysis of the two years would be untenable. Tournament combats provide high-scoring competitors with an extremely useful form of training. But the workload a competitor accrues in combat in any given year may affect his results for the next year's starting activity. It does not appear viable to simulate all the conditions that occur in combat in the training situation. We are of the opinion that no definitive conclusions can be drawn on the basis of the material available. Before such conclusions right be reached it would be necessary to carry out individual analyses of particular competitors' workloads during training and combat, and to augment the range of research with results observed for their respective parameters for technical and tactical skills, body build, fitness, etc., and also to take their opponents into account.